The Employment Policy in the Mining Industry: A Critical Study on Gender Discrimination - Mohsen, Brahmi; Zouari, Sonia (Journal of Asian Business Strategy, 2014)
The object of this paper is devoted to test for the presence of gender discrimination of hiring, in one of the main important economy sector of Tunisia, which is the Tunisian mining industry in the Southwest inmate fully by the largest public mining Firm TPGC (1897), which is, in fact, the only industrial pole of employability of young scholars graduates in this region of the Tunisian mining Basin. The result of this study proves that is no equity between the two genders. The reason of this segregation in favor the masculine gender returns to the specificity of this mining sector that depends more in the physical efforts than mental practices.